Evaluation of electrical capacitance tomography thresholding techniques for void fraction measurement of gas-liquid system - Sow Mei, I.L. (Trans Tech Publications Ltd, 2014)
An analysis on the void fraction measurement for binary phase gas-liquid dielectric materials inside an Electrical Capacitance Tomography (ECT) sensor has been performed on the tomogram images by using different thresholding techniques. The analysis is pertinent to improve the accuracy of the application of thresholding technique for void fraction measurements in pipelines and reactors since the currently available information is limited in terms of accuracy. This preliminary investigation was performed to evaluate the accuracy of three different thresholding algorithms: Otsuâs, Niblackâs and Kuoâs Method based on the void fraction measurement for a binary phase oil-air system. The experimental and image processing analysis enables one to determine the optimal threshold method by selecting the threshold algorithm which produces the highest accuracy and consistency in the void fraction measurement as compared to the actual value. Â© 2014 Trans Tech Publications, Switzerland.